2023
DOI: 10.1038/s41598-022-24940-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific identification of genome-wide DNA-methylation differences between intracranial and extracranial melanoma metastases

Abstract: Melanomas frequently metastasize to distant organs and especially intracranial metastases still represent a major clinical challenge. Epigenetic reprogramming of intracranial metastases is thought to be involved in therapy failure, but so far only little is known about patient-specific DNA-methylation differences between intra- and extracranial melanoma metastases. Hierarchical clustering of the methylomes of 24 patient-matched intra- and extracranial melanoma metastases pairs revealed that intra- and extracra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…However, melanoma metastases in different organs from a patient are more similar to each other than to metastases from other patients in the same organs. This patient-specific heterogeneity of molecular data from melanoma metastases has been observed in other studies before [18,24,25]. Therefore, such differences between individual patients should be included in the data analysis to further improve the identification of molecular differences between intra-and extracranial melanoma metastases.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, melanoma metastases in different organs from a patient are more similar to each other than to metastases from other patients in the same organs. This patient-specific heterogeneity of molecular data from melanoma metastases has been observed in other studies before [18,24,25]. Therefore, such differences between individual patients should be included in the data analysis to further improve the identification of molecular differences between intra-and extracranial melanoma metastases.…”
Section: Introductionmentioning
confidence: 62%
“…Fischer et al [26] performed RNA sequencing and multiple immune-relevant sequencing analyses and identified a significant immunosuppression and enrichment of oxidative phosphorylation in intracranial melanoma metastases. We have recently performed a personalized analysis of genome-wide DNA-methylation profiles and revealed a global decrease of DNA-methylation intracranially [25]. These DNA-methylation changes between patient-matched intra-and extracranial melanoma metastases affected many genes involved in cellular signaling, growth, adhesion and apoptosis and further supported the presence of a neuronal phenotype.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…According to the literature review, there is no difference in methylation between methylation level and location 31 , 42 , 43 . Some papers found that previous therapy had no effect on methylation levels 31 , 44 , and in our analysis, we recruited a melanoma patient who had not previously received treatment. Finally, the study's results were unaffected by age, tumour location, or treatment experience.…”
Section: Discussionmentioning
confidence: 99%
“…This facet of the technology is unique amongst epigenetic profiling approaches and particularly aligns Active-Seq with recent work highlighting the significance of unmethylated enhancer DNA as a signature of cell biology 12 . Enhancers are partially (10-60%) methylated in healthy cells and their differential methylation is, in fact, the prevalent perturbation to methylation of DNA at 'functional' genomic elements [62][63][64] . In cancer, hypomethylation of enhancers is more common, being approximately twice as prevalent, in broad range of cancers, as enhancer hypermethylation 62 .…”
mentioning
confidence: 99%